Base Composition and Hybridization Studies of the Three Double-Stranded RNA Segments of Bacteriophage φ6 - Van Etten, J. L. (1974)
The three double-stranded ribonucleic acid (dsRNA) segments of the bacteriophage φ6 were isolated and shown to have similar melting temperatures and base compositions. RNA:RNA hybridization experiments with the isolated segments eliminate the possibility that the two smaller dsRNA segments arise from a cleavage of the large dsRNA segment. The two smaller RNA segments reanneal rapidly even at low temperatures; in contrast, the large dsRNA reannealed only at higher temperatures. Evidence is also presented which suggests that the dsRNAs may contain a short single-stranded RNA tail.